Adaptogenic-active components from Kaempferia parviflora rhizomes - Patcharee Pripdeevech (2018)
Kaempferia parviflora rhizome extracts obtained by maceration with hexane, chloroform, methanol, and ethanol were screened for their adaptogenic activities using swimming tests of mice. The effective adaptogenic extract dose was 500 mg/kg of body weight and was given orally once a day. Crude hexane extract showed significantly shorter mouse immobilisation time than those of the other and control extracts. This crude hexane extract was separated into three fractions by column chromatography. Among these fractions, the fraction rich in terpenoids possessed the highest adaptogenic activity and was comparable to that of the crude ginseng root powder used as a reference control. Therefore, terpenes contained in this fraction could be attributed to the decrease in exhaustion during the swimming of mice. There was no effect on body weight, heart, liver, kidneys, and adrenal glands of the mice. Chemical characterisation of this adaptogenic-active fraction by NMR and GC-MS showed germacene D, β-elemene, α-copaene, and E-caryophyllene as major constituents. Accordingly, these terpenes are considered the adaptogenic agents of K. parviflora rhizomes. © 2011 Elsevier Ltd. All rights reserved.